Die Morfologie van die vroulike strobilus en embriologie van die genus Podocarpus L'Herit. ex Pers. in Suid-Afrika - Vvan der Schijff, H. P. (University of Pretoria, 2014)
Thesis (PhD)--University of Pretoria, 1977.